Protection of Retinal Ganglion Cells and Retinal Vasculature by Lycium Barbarum Polysaccharides in a Mouse Model of Acute Ocular Hypertension - Mi, Xue-Song; Feng, Qian; Lo, Amy Cheuk Yin; Chang, Raymond Chuen-Chung; Lin, Bin; Chung, Sookja Kim; So, Kwok-Fai (PloS one, 2012)
Acute ocular hypertension (AOH) is a condition found in acute glaucoma. The purpose of this study is to investigate the protective effect of Lycium barbarum polysaccharides (LBP) and its protective mechanisms in the AOH insult. LBP has been shown to exhibit neuroprotective effect in the chronic ocular hypertension (COH) experiments. AOH mouse model was induced in unilateral eye for one hour by introducing 90 mmHg ocular pressure. The animal was fed with LBP solution (1 mg/kg) or vehicle daily from 7 days before the AOH insult till sacrifice at either day 4 or day 7 post insult. The neuroprotective effects of LBP on retinal ganglion cells (RGCs) and blood-retinal-barrier (BRB) were evaluated. In control AOH retina, loss of RGCs, thinning of IRL thickness, increased IgG leakage, broken tight junctions, and decreased density of retinal blood vessels were observed. However, in LBP-treated AOH retina, there was less loss of RGCs with thinning of IRL thickness, IgG leakage, more continued structure of tight junctions associated with higher level of occludin protein and the recovery of the blood vessel density when compared with vehicle-treated AOH retina. Moreover, we found that LBP provides neuroprotection by down-regulating RAGE, ET-1, Aβ and AGE in the retina, as well as their related signaling pathways, which was related to inhibiting vascular damages and the neuronal degeneration in AOH insults. The present study suggests that LBP could prevent damage to RGCs from AOH-induced ischemic injury; furthermore, through its effects on blood vessel protection, LBP would also be a potential treatment for vascular-related retinopathy.